2011
DOI: 10.1186/gb-2011-12-2-r15
|View full text |Cite
|
Sign up to set email alerts
|

A statistical framework for modeling gene expression using chromatin features and application to modENCODE datasets

Abstract: We develop a statistical framework to study the relationship between chromatin features and gene expression. This can be used to predict gene expression of protein coding genes, as well as microRNAs. We demonstrate the prediction in a variety of contexts, focusing particularly on the modENCODE worm datasets. Moreover, our framework reveals the positional contribution around genes (upstream or downstream) of distinct chromatin features to the overall prediction of expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
154
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(173 citation statements)
references
References 63 publications
17
154
2
Order By: Relevance
“…Previous work has shown that prediction of factor-responsive targets from an individual ChIP-seq experiment can be improved by incorporating additional information, such as co-correlated expression across hundreds of different microarray studies (Lai et al 2010;Cheng et al 2011;Marbach et al 2012). Here, we show that by integrating 98 ChIP-seq data sets for 57 transcription factors, we can identify low-complexity binding sites that significantly improve the fraction of factor-responsive targets.…”
Section: Low-complexity Targets Correlate Better With Factor-responsimentioning
confidence: 78%
See 1 more Smart Citation
“…Previous work has shown that prediction of factor-responsive targets from an individual ChIP-seq experiment can be improved by incorporating additional information, such as co-correlated expression across hundreds of different microarray studies (Lai et al 2010;Cheng et al 2011;Marbach et al 2012). Here, we show that by integrating 98 ChIP-seq data sets for 57 transcription factors, we can identify low-complexity binding sites that significantly improve the fraction of factor-responsive targets.…”
Section: Low-complexity Targets Correlate Better With Factor-responsimentioning
confidence: 78%
“…Compendia of ChIP-seq data sets can be used to construct regulatory networks and to find novel pairs of transcription factors with similar sets of bound targets that suggest new cases of transcription factor co-association (Niu et al 2011;Gerstein et al 2012). Additionally, in combination with data sets describing histone modifications and other measures of chromatin state, such compendia can be used to predict gene expression (Cheng et al 2011Marbach et al 2012). These examples illustrate how combining data for many transcription factors can provide emergent insights about gene regulation that cannot be found by studying one factor by itself.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Recently, additional methods have been developed to predict expression from histone ChIP-seq [22][23][24][25] . These methods were used to predict RNA-seq-based expression levels, using a large number of histone ChIP-seq data sets as input.…”
Section: Npgmentioning
confidence: 99%
“…We have previously shown that histone modifications are strong indicators of expression levels [46,47]. Therefore, we next explored the relationship between DNA methylation and histone modifications in terms of indicating gene expression, and tested whether information on gene expression conveyed by DNA methylation is totally subsumed by that of histone modifications.…”
Section: Quantitative Relationship With Histone Modificationsmentioning
confidence: 99%